Dear sister: a memoir of secrets, survival, and unbreakable bonds - Horton, Michelle (GCP, Grand Central)
"In September 2017, a knock on the door upends Michelle Horton's life forever: her sister had just shot her partner and was now in jail. During the investigation that follows, Michelle learns that Nikki had been hiding horrific abuse for years. Stunned to find herself in a situation she'd only ever encountered on television and true crime podcasts, Michelle rearranges her life to care for Nikki's children and simultaneously launches a fight to bring Nikki home, squaring off against a criminal justice system seemingly designed to punish the entire family. In this exquisite memoir, Michelle retraces the sisters' childhood and explores how so many people, including herself, could have been blind to the abuse. An intimate look at a family surviving trauma, Dear Sister is a deeply personal story about what it takes to be believed and the danger of keeping truths hidden. Ultimately, Horton turns her family's suffering into hard won wisdom: a profound story of resilience and the unbreakable bond between sisters"--